Handling food safely - Video Education Australasia (Bendigo, Vic.: Video Education Australasia, 1995)
Looks at the subject of food handling within a commercial kitchen environment. Shows the measures which must be taken in order to operate a safe hygenic kitchen, free of food contamination
Keywords: Food Contamination -- prevention & control; Food service -- Sanitation; Food handling